Sleep duration and timing are associated with next-day physical activity: Insights from two large-scale wearable sensor studies - Josh Leota; Mark É. Czeisler; Flora Le; David M. Presby; Emily R. Capodilupo; Hannah Scott; Joshua F. Wiley; Sean P. A. Drummond; Shantha M. W. Rajaratnam; Elise R. Facer-Childs (Proceedings of the National Academy of Sciences, 2025)
Sleep and physical activity (PA) are pillars of health. However, the temporal dynamics between these two behaviors remain poorly understood. This research aims to examine the independent and interactive between- and within-person associations of sleep duration and sleep onset timing on next-day PA duration in two large, longitudinal samples of adults under free-living conditions. In the primary study, participants (N = 19,963; 5,995,080 person-nights) wore a validated biometric device (WHOOP) for 1 y (01/09/2021 to 31/08/2022). Objective sleep and PA metrics were derived from the wrist-worn device. Generalized additive mixed models assessed between- and within-person associations between sleep and PA variables, adjusted for age, sex, Body Mass Index, weekday/weekend, seasonal effects, biometric feedback, and autocorrelated errors. Between participants, longer sleep duration and later sleep onset timing were associated with decreased moderate-to-vigorous PA (MVPA) and overall PA duration ( ps < 0.001). Within participants, sleeping shorter-than-usual and falling asleep earlier-than-usual were associated with increased next-day MVPA and overall PA, whereas sleeping longer-than-usual, or falling asleep later-than-usual, showed the opposite relationship ( ps < 0.001). Next-day MVPA duration was highest following earlier-than-usual sleep onset timing combined with one’s typical sleep duration. Results were consistent but smaller in magnitude in the external validation study (N = 5,898; 635,477 person-nights) using Fitbit data from the All of Us Research Program. Individuals may sacrifice time in one health behavior for time in the other. Interventions promoting exercise and holistic public health messaging should consider the temporal dynamics between sleep and next-day PA outcomes.